Privatisation of government services in Australia: what is known about health and equity impacts - Julia Anaf; Toby Freeman; Fran Baum (BMC, 2024)
Abstract Background Historically in Australia, all levels of government created collective wealth by owning and operating infrastructure, and managing natural assets, key public goods and essential services while being answerable to the public. This strong state tradition was challenged in the 1980s when privatisation became a widespread government approach globally. Privatisation involves displacing the public sector through modes of financing, ownership, management and product or service delivery. The Australian literature shows that negative effects from privatisation are not spread equitably, and the health and equity impacts appear to be under-researched. This narrative overview aims to address a gap in the literature by answering research questions on what evidence exists for positive and negative outcomes of privatisation; how well societal impacts are evaluated, and the implications for health and equity. Methods Database and grey literature were searched by keywords, with inclusion criteria of items limited to Australia, published between 1990 and 2022, relating to any industry or government sector, including an evaluative aspect, or identifying positive or negative aspects from privatisation, contracting out, or outsourcing. Thematic analysis was aided by NVivo qualitative data software and guided by an a-priori coding frame. Results No items explicitly reflected on the relationship between privatisation and health. Main themes identified were the public cost of privatisation, loss of government control and expertise, lack of accountability and transparency, constraints to accessing social determinants of health, and benefits accruing to the private sector. Discussion Our results supported the view that privatisation is more than asset-stripping the public sector. It is a comprehensive strategy for restructuring public services in the interests of capital, with privatisation therefore both a political and commercial determinant of health. There is growing discussion on the need for re-nationalisation of certain public assets, including by the Victorian government. Conclusion Privatisation of public services is likely to have had an adverse impact on population health and contributed to the increase in inequities. This review suggests that there is little evidence for the benefits of privatisation, with a need for greater attention to political and commercial determinants of health in policy formation and in research.